Analytical solutions for elastic response of coated mesoporous materials to pore pressure. (October 2016) - Liu, Mingchao; Zhang, Yafei; Wu, Jian; Gan, Yixiang; Chen, C.Q.
Abstract: Pore fluid adsorption-induced deformation of mesoporous materials is an important physical phenomenon. Experimental results show that the adsorption-induced elastic deformation can be quantified in terms of pore-load modulus (i.e., the radio between pore pressure and overall strain). In practical applications, most mesoporous materials are functionalized by post-fabrication processes such as surface coating. In this paper, we develop a theoretical model to predict the adsorption-induced deformation of ordered mesoporous materials with uniform and functionally graded coatings. Closed-form solutions of the pore-load modulus are obtained as a function of porosity, elastic properties of bulk materials and coating phases, thickness of coating, and geometrical arrangement of pores. Deformation of a coated triangular lattice of cylindrical pores representing the mesoporous materials with inner fluid pressure is also simulated by the finite element method, showing excellent agreement with the established theoretical solutions. The proposed model provides a general description of the elastic response of heterogeneous mesoporous materials subjected to the inner pressure loading.